Design of hybrid sliding mode controller based on fireworks algorithm for nonlinear inverted pendulum systems. (December 2016) - Su, Te-Jen; Wang, Shih-Ming; Li, Tsung-Ying; Shih, Sung-Tsun; Hoang, Van-Manh
The objective of this article is to optimize parameters of a hybrid sliding mode controller based on fireworks algorithm for a nonlinear inverted pendulum system. The proposed controller is a combination of two modified types of the classical sliding mode controller, namely, baseline sliding mode controller and fast output sampling discrete sliding mode controller. The simulation process is carried out with MATLAB/Simulink. The results are compared with a published hybrid method using proportional–integral–derivative and linear quadratic regulator controllers. The simulation results show a better performance of the proposed controller.